The Question of Descriptors for Academic Writing in European Language Framework: a Critical View - Neff, JoAnne; Bunce, Caroline; Dafouz, Emma; Gallego, Javier; Rica, Juan Pedro; Genis, Marta; McCabe, Anne (Kalbotyra, 2008)
Since the 1960s, with the influx of a great number of students, both native and non-native, with little experience in formal academic discourse, universities in the English-speaking world have become increasingly aware of the need to offer specific instruction in writing skills. This situation required a clearer definition of what the characteristics of this particular type of writing might be (Grabe & Kaplan 1996) and it became apparent that many of the existing teaching materials concentrated overly on normative, grammatical considerations and not on a broader perspective based on discursive competence. Therefore, since the 1990s, there has been more emphasis on the analysis of the rhetorical conventions of various genres, including cross-linguistic comparisons (Connor 1995; Flowerdew 2000; Hyland 2002; Neff et al. 2004; Neff and Dafouz 2008). Because of the utilization of English as a “lingua franca” in the global community (Gnutzman and Intemann 2005) and the growth of student exchange programs within Europe, it has become progressively evident that both students and teachers require a clear set of guidelines, such as those provided by the EU framework descriptors for various areas of linguistic competency. But, as the difficulties experienced by non-native writers of academic English are very genre specific and appear to be largely independent of purely linguistic competency (many native novice writers also find academic writing problematic), the EU descriptors for academic work are too broad for the type of writing that our students must carry out in tertiary institutions. While much work is clearly being done within universities and colleges to address the prototypical academic writing skills in English, it would be helpful for all concerned if more specific guidelines could be shared. Thus, one major aim of this study is to draw up a series of structural and rhetorical descriptors and evaluate our students’ written production before and after using them in order to test their relevance for our syllabus and perhaps for use by a wider audience in the future.